Effect of sago palm waste compost and SP-36 fertilizer against fractionation of P on Ultisols. (December 2019) - Kaya, E; Putinella, J A; Puturuhu, F.
Abstract: Ultisol is a marginal type of soil that is acidic, which is mostly cultivated for agricultural areas. Nevertheless this type of soil has many obstacles, especially from the chemical and physical properties of the soil. Some of the chemical constraints faced in the use of Ultisol soil include: low soil pH (acidic soil reaction), nutrient content especially low P nutrients and high interchangeable Al concentrations. High interchangeable Al can bind P to form Al-P (Strengit) compounds so that the P concentration in the soil solution is reduced and consequently plants lack P, besides that high metal content can poison / cause toxicity to plants so that plant growth becomes unfavorable. One effort to increase P soil solution and reduce P stability is the application of P fertilizer, but it must be accompanied by organic matter. Giving organic material to acid soils can produce organic acids that are capable of chelating Al metal so that P will be released from soil solubility and available in soil solution. The research was conducted in the laboratory analysis of soil, water and plants, as well as greenhouse Faperta Unpatti Ambon, which lasted from March - November, 2011. This study used a complete randomized design with 2 factors factorial pattern consisting of the first factor is the maturity of Sago pith Waste compost and the second factor is the phosphate fertilizer (SP-36). Other research results indicate that administration of sago pith waste Compost can independently reduce Fe-P compounds. Granting SP-36 can independently reduce Fe-P compounds. Provision of compost ell sago together with SP-36 can increase the Ca-P compounds from 17.87 to 38.53 ppm, and Al-P compounds decrease from 35.00 to 16.67 ppm.